INCLUSION OF KAPOK SEED OIL IN THE DIET FOR GROWING OF THIN-TAILED SHEEP TO REDUCE CHOLESTEROL AND TO IMPROVE OMEGA-SIX FATTY ACID CONTENTS OF LAMB - Widiyanto, W.; Soejono, M.; Hartadi, H.; Bachrudin, Z.; Surahmanto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
This research was conducted to study the influence of protected kapok seed oil (PKSO)supplementation in its combination with concentrate, in this case was rice bran (RB) on lipid content ofthin tailed sheep received field grass as basal feed. A number of 24 heads of male thin-tailed sheep wereused as experimental material. These sheep were divided into 8 treatment groups. There were twotreatment factors, i.e. : PKSO supplementation (S) as factor I and RB supplementation (K) as factor II.Factor I consisted of 2 levels, i.e. 0% (S0) and 10% (S1), whereas factor II consist of 4 levels, i.e. 0%(K0), 15% (K1), 30% (K2) and 45% (K3), respectively, based on dry matter (DM) intake. Severalvariables were measured, namely content of intra muscular fat (IMF), iodine number of muscular fattyacid, content of meat cholesterol and omega 6 fatty acid (in this case linoleic acid). The collected datawere statistically analyzed by analysis of variance with factorial treatment pattern (2 x 4) in completelyrandomized design (CRD). Content of IMF in sheep supplemented with 0 and 15% KSO levels was notsignificantly different from those without kapok seed oil (KSO) supplementation at the same level ofRB feeding (3.45 and 3.99% vs 3.01 and 3.75%). Supplementation of protected KSO in combinationwith 30 and 45% RP resulted in significantly increased (P < 0.05) IMF content (4.75 and 5.93% vs 4.32and 5.40%) and significantly decreased (P < 0.05) meat chollesterol content (62.46 and 65.26 mg/100 g vs 89.21 and 72.63 mg/100 g ) also significantly increased (P < 0.05) linoleic acid proportion (15.52 and18.25% vs 3.68 and 4.04%) and iodine number (12.52 and 10.25 vs 4.09 and 4.98).